Pasteurella multocida infection unrelated to animal bites as a cause of septic shock in a liver cirrhosis patient: A case report - Waramit, Sirayut (Journal of Medicine and Health Sciences, 2023)
A gram-negative bacteria known as Pasteurella multocida is morphologically classified as a coccobacillus. It is among the most prevalent organisms that infect pet bites. However, even without animal bites or scratches, serious illnesses can still develop. Humans are susceptible to Pasteurella multocida, particularly those with weakened immune systems. Few cases in the literature, particularly in cirrhotic patients, point to Pasteurella multocida as the primary cause of septic shock. This study consisted of a 48 year-old male patient, who had no prior history of animal exposure, presented with fever, abdominal pain and an altered mental status, then developed septic shock due to Pasteurella multocida bacteremia. After treatments of ventilation and antibiotics, the patient recovered and was discharged from the hospital.